Population genomic structure in Goodman's mouse lemur reveals long‐standing separation of Madagascar's Central Highlands and eastern rainforests - George P. Tiley; Tobias van Elst; Helena Teixeira; Dominik Schüßler; Jordi Salmona; Marina B. Blanco; José M. Ralison; Blanchard Randrianambinina; Rodin M. Rasoloarison; Amanda R. Stahlke; Paul A. Hohenlohe; Lounès Chikhi; et al. (Molecular Ecology, 2022)
Madagascar's Central Highlands are largely composed of grasslands, interspersed with patches of forest. The historical perspective was that Madagascar's grasslands had anthropogenic origins, but emerging evidence suggests that grasslands were a component of the pre‐human Central Highlands vegetation. Consequently, there is now vigorous debate regarding the extent to which these grasslands have expanded due to anthropogenic pressures. Here, we shed light on the temporal dynamics of Madagascar's vegetative composition by conducting a population genomic investigation of Goodman's mouse lemur ( Microcebus lehilahytsara ; Cheirogaleidae). These small‐bodied primates occur both in Madagascar's eastern rainforests and in the Central Highlands, making them a valuable indicator species. Population divergences among forest‐dwelling mammals will reflect changes to their habitat, including fragmentation, whereas patterns of post‐divergence gene flow can reveal formerly wooded migration corridors. To explore these patterns, we used RADseq data to infer population genetic structure, demographic models of post‐divergence gene flow, and population size change through time. The results offer evidence that open habitats are an ancient component of the Central Highlands, and that widespread forest fragmentation occurred naturally during a period of decreased precipitation near the last glacial maximum. Models of gene flow suggest that migration across the Central Highlands has been possible from the Pleistocene through the recent Holocene via riparian corridors. Though our findings support the hypothesis that Central Highland grasslands predate human arrival, we also find evidence for human‐mediated population declines. This highlights the extent to which species imminently threatened by human‐mediated deforestation may already be vulnerable from paleoclimatic conditions.

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Kinematic and Somatosensory Gains in Infants with Cerebral Palsy After a Multi-Component Upper-Extremity Intervention: A Randomized Controlled Trial - Nathalie L. Maitre; Arnaud Jeanvoine; Paul J. Yoder; Alexandra P. Key; James C. Slaughter; Helen Carey; Amy Needham; Micah M. Murray; Jill Heathcock; Stephanie Burkhardt; Lelia Emery; Kaleigh Hague; et al. (Brain Topography, 2020)

Neonatal Multisensory Processing in Preterm and Term Infants Predicts Sensory Reactivity and Internalizing Tendencies in Early Childhood - Nathalie L. Maitre; Alexandra P. Key; James C. Slaughter; Paul J. Yoder; Mary Lauren Neel; Céline Richard; Mark T. Wallace; Micah M. Murray (Brain Topography, 2020)
Multisensory processes include the capacity to combine information from the different senses, often improving stimulus representations and behavior. The extent to which multisensory processes are an innate capacity or instead require experience with environmental stimuli remains debated. We addressed this knowledge gap by studying multisensory processes in prematurely born and full-term infants. We recorded 128-channel event-related potentials (ERPs) from a cohort of 55 full-term and 61 preterm neonates (at an equivalent gestational age) in response to auditory, somatosensory, and combined auditory-somatosensory multisensory stimuli. Data were analyzed within an electrical neuroimaging framework, involving unsupervised topographic clustering of the ERP data. Multisensory processing in full-term infants was characterized by a simple linear summation of responses to auditory and somatosensory stimuli alone, which furthermore shared common ERP topographic features. We refer to the ERP topography observed in full-term infants as “typical infantile processing” (TIP). In stark contrast, preterm infants exhibited non-linear responses and topographies less-often characterized by TIP; there were distinct patterns of ERP topographies to multisensory and summed unisensory conditions. We further observed that the better TIP characterized an infant’s ERPs, independently of prematurity, the more typical was the score on the Infant/Toddler Sensory Profile (ITSP) at 12 months of age and the less likely was the child to the show internalizing tendencies at 24 months of age. Collectively, these results highlight striking differences in the brain’s responses to multisensory stimuli in children born prematurely; differences that relate to later sensory and internalizing functions.

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Somatosensory Event-Related Potentials and Association with Tactile Behavioral Responsiveness Patterns in Children with ASD - Carissa J. Cascio; Chang Gu; Kimberly B. Schauder; Alexandra P. Key; Paul Yoder (Brain Topography, 2015)

Angiopoietin-like protein 2 regulates endothelial colony forming cell vasculogenesis - Matthew R. Richardson; Emilie P. Robbins; Sasidhar Vemula; Paul J. Critser; Catherine Whittington; Sherry L. Voytik-Harbin; Mervin C. Yoder (Angiogenesis, 2014)

Safety and Health in Biomass Production, Transportation, and Storage: A Commentary Based on the Biomass and Biofuels Session at the 2013 North American Agricultural Safety Summit - Aaron M. Yoder; Charles Schwab; Paul Gunderson; Dennis Murphy (Journal of Agromedicine, 2014)

A model for pro‐poor wealth creation through small‐plot irrigation and market linkages - John Magistro; Michael Roberts; Steve Haggblade; Fritz Kramer; Paul Polak; Elizabeth Weight; Robert Yoder (Irrigation and Drainage, 2007)
This paper relates the field experience of an international NGO in strengthening linkages between irrigation development and poverty reduction. Poverty Reduction through Irrigation and Smallholder Markets (PRISM) is introduced as a methodology for combining small‐plot irrigation technology with complementary inputs and services to enhance small farmers' ability to participate effectively in markets for high‐value agricultural commodities. Data from field projects in Nepal and India indicate that the PRISM approach can lead to significant additional income for small farmers and other micro and small enterprises in agricultural value chains. Copyright © 2007 John Wiley & Sons, Ltd.

Creating wealth from groundwater for dollar-a-day farmers: Where the silent revolution and the four revolutions to end rural poverty meet - Paul Polak; Robert Yoder (Hydrogeology Journal, 2006)

MUSCLE-DERIVED CD45−SCA-1+C-KIT− PROGENITOR CELLS GIVE RISE TO SKELETAL MUSCLE MYOTUBES IN VITRO - CASSANDRE L. ROYER; JONATHAN C. HOWELL; PAUL R. MORRISON; EDWARD F. SROUR; MERVIN C. YODER (In Vitro Cellular & Developmental Biology - Animal, 2002)